REFORMISMO Y RENOVACIÓN EDUCATIVA: TRAYECTORIAS UNIVERSITARIAS Y PARTICIPACIÓN ESTUDIANTIL EN TORNO A LA DOCENCIA LIBRE EN LA FACULTAD DE CIENCIAS MÉDICAS DE LA UNIVERSIDAD DE BUENOS AIRES (De Signos y Sentidos, 2018)
A series of initiatives that considered the cultural, educational and scientific renovation of institutions of higher learning were included within the postulates of the University Reform. To achieve this enterprise, while relying on the different university models of European origin, free teaching was one of the principles defended by the reformists. This article inquired into the implementation of free teaching at the Universidad de Buenos Aires Medicine College with the purpose of illustrating two issues. On the one hand, this measure was analyzed within the vast reformist agenda while taking into account the different stances and the repercussion of free teaching inside students’ life. On the other hand, it is enquired if this regime of university teaching implied an opening process in the access to professorships. In order to achieve this, official documents, university magazines and a series of academic files about a group of graduates who requested access to teaching after the statute reform of 1918 were used as sources. The proposed approach links the analysis about the modalities of student intervention on academic politics with the graduates’ practices and trajectories, who had access to college after the University Reform.
Keywords: free teaching; University Reform; Universidad de Buenos Aires; Medicine